Extraction of rare earth element using synergist extractant immobilised resins (SEIR) - Sumaiya, Zainal Abidin; Nur Nadiatul Hidayah, Shaikh Rohmat (2018)
Extraction of REE using new combination of synergi st extractant between conventional extractant with ionic liquid. Improvise the convention-al technique in extraction of REE from LLE into SLE using industrial resin immobilised with synergist extractant.